1,25-dihydroxyvitamin D3 protects against macrophage-induced activation of NFκB and MAPK signalling and chemokine release in human adipocytes. - Cherlyn Ding; John P H Wilding; Chen Bing (PLoS ONE)
Increased accumulation of macrophages in adipose tissue in obesity is linked to low-grade chronic inflammation, and associated with features of metabolic syndrome. Vitamin D3 may have immunoregulatory effects and reduce adipose tissue inflammation, although the molecular mechanisms remain to be established. This study investigated the effects of vitamin D3 on macrophage-elicited inflammatory responses in cultured human adipocytes, particularly the signalling pathways involved. Macrophage-conditioned (MC) medium (25% with adipocyte maintenance media) markedly inhibited protein expression of the nuclear factor-κB (NFκB) subunit inhibitor κBα (IκBα) (71%, P<0.001) and increased NFκB p65 (1.5-fold, P = 0.026) compared with controls. Treatment with 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) abolished macrophage-induced activation of NFκB signalling by increasing IκBα expression (2.7-fold, P = 0.005) and reducing NFκB p65 phosphorylation (68%; P<0.001). The mitogen-activated protein kinase (MAPK) signalling was activated by MC medium, which was also blunted by 1,25(OH)2D3 with a downregulation of phosphorylated p38 MAPK (32%, P = 0.005) and phosphorylated Erk1/2 (49%, P = 0.001). Furthermore, MC medium (12.5% or 25%) dose-dependently upregulated secretion of key proinflammatory chemokines/cytokines (22-368-fold; all P<0.001) and this was significantly decreased by 1,25(OH)2D3: IL-8 (61% and 31%, P<0.001), MCP-1 (37%, P<0.001 and 36%, P = 0.002), RANTES (78% and 62%, P<0.001) and IL-6 (29%, P<0.001 and 34%, P = 0.019). Monocyte migration-elicited by adipocytes treated with 1,25(OH)2D3 was also reduced (up to 25%, P<0.001). In conclusion, vitamin D3 could be anti-inflammatory in adipose tissue, decreasing macrophage-induced release of chemokines and cytokines by adipocytes and the chemotaxis of monocytes. Our data suggests these effects are mediated by inhibition of the NFκB and MAPK signalling pathways.